shRNAs targetting LRP mRNA as alternative therapeutic tools for Alzheimer's disease treatment - Gonsalves, Danielle (My University, 2013)
Alzheimer’s disease (AD) is the most prevalent neurodegenerative disease affecting in excess of 26.6 million individuals globally. The neuropathological features of AD include extracellular deposition of amyloid beta (Aβ) plaques and intracellular neurofibrillary tangle formation. The cellular prion protein (PrPC) regulates the amyloidogenic cleavage pathway involved in Aβ shedding and interacts with the Aβ peptide. Given these interactions, the aim of this study was to investigate the influence of the 37kDa/67kDa laminin receptor (LRP/LR)- the cellular receptor for prion proteins- on Aβ shedding. Transfection of HEK293 cells with short hairpin RNAs (shRNAs) directed against LRP mRNA significantly decreased LRP levels in addition to Aβ shedding. Flow cytometric analysis revealed unchanged cell surface levels of the amyloid precursor protein (APP), β-secretase and γ-secretase after transfection of cells with shRNAs, suggesting a role of LRP/LR in Aβ shedding via a mechanism independent of gene-expression modulation of these key proteins. LRPshRNA treatment significantly reduced sAPPβ expression, implicating LRP/LR in APP processing specifically via augmenting the activity of β-secretase. Colocalisation of LRP/LR with APP, β- and γ-secretase, respectively, alludes to a possible interaction between said proteins. Therefore, LRP-shRNAs are suggested as alternative therapeutic tools for AD treatment.
A!dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in the fulfillment of the requirements for the degree of Master of Science. 2013.
Keywords: Alzheimer's disease.; Alzheimer Disease - drug therapy.